Building bushfire resilience in horticultural production systems: important insights from Australia - Idowu, Oluyoye; Pitt, Tim; Dodds, Kevin; Golding, John; Fearnley, Jessica; Petrie, Paul; Holzapfel, Bruno (Frontiers in Sustainable Food Systems, 2023)
Extreme bushfire is having considerable negative effects on the sustainability of agricultural landscapes in various parts of the world. Fire-induced damages to tree crops have led to significant effects on perennial horticultural production systems with associated lower returns and decline in economic sustainability. Australia is one of the most fire-prone countries in the world and contributes to global horticultural production with production forecast level estimated at 18.2 billion in 2023–24, according to the Australian Department of Agriculture, Fisheries and Forestry. Bushfire-related damages to horticultural production may however threaten this promising potential. This review provides a commentary on the history, scale and impacts of extreme bushfires in Australia. The effects of bushfire on horticulture, including soil nutrient availability, fruit tree physiology and carbohydrate sink-source dynamics are discussed. Given the increasing frequency and severity of bushfires as a result of climate change, the negative effects of heat and fire damage on fruit tree production are expected to increase. Based on the Australian experience with bushfires in horticultural landscapes, this review outlines proactive responses for minimising bushfire impacts on horticultural production in temperate regions, with particular reference to the Rosaceae family. Adaptation strategies must be planned and set up before orchard establishment and should include defensible space or safety zones around the orchard, as well as internal and external fuel reduction strategies for the orchard lifespan.